1999
DOI: 10.1093/jn/129.10.1862
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Fish Oil Leads to Prompt Incorporation of Eicosapentaenoic Acid into Colonic Mucosa of Patients Prior to Surgery for Colorectal Cancer, But Has No Detectable Effect on Epithelial Cytokinetics

Abstract: Fish oil (FO) was previously reported to partially normalize colorectal crypt cell cytokinetics in patients with colorectal neoplasms. We determined the effect of FO on the fatty acid composition of colonic mucosa and mesenteric adipose tissue and on rectal crypt cell proliferation in patients undergoing surgery for colonic carcinoma. Patients (49-28 males; 21 females) were randomly assigned to consume FO capsules (2 g b.d.; FO group) containing 1.4 g eicosapentaenoic acid (EPA) and 1.0 g docosahexaenoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…However this is likely to be rapidly metabolised by the luminal bacteria and the significant increase of n-3 PUFAs in colonic mucosa after alimentary supplementation is assumed to be absorbed from the blood where concentrations may reach as high as 400 lmol/l following supplementation [45][46][47]. We have therefore taken a novel ex vivo biomarker approach to investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…However this is likely to be rapidly metabolised by the luminal bacteria and the significant increase of n-3 PUFAs in colonic mucosa after alimentary supplementation is assumed to be absorbed from the blood where concentrations may reach as high as 400 lmol/l following supplementation [45][46][47]. We have therefore taken a novel ex vivo biomarker approach to investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In total, we n23 PUFAs IN CANCER, SURGERY, AND CRITICAL CARE retrieved 23 RCTs and 13 open-label studies that reported incorporation or washout in cancer, surgery, and critical care after supplementation of n23 FAs via fish-oil capsules (7,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), ONSs (4,17,20,26,60), and/or enteral nutrition (23,24,26), or n23 FA lipid emulsions for parenteral administration (27,32,33,37,40,(61)(62)(63)(64) (see Supplemental Tables 1-3 under ''Supplemental data'' in the online issue). The following paragraphs summarize the most important findings.…”
Section: Incorporation and Washout Of N23 Fas After Supplementationmentioning
confidence: 99%
“…Eight RCTs reported on the incorporation and washout in patients who underwent surgery after enteral supplementation (24,26,56) or parenteral supplementation of n23 FAs (27,32,33,61,62) (see Supplemental Table 2 under ''Supplemental data'' in the online issue).…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations